Theoretical study of the effects of the shape of the spinning triangle. Issue 3 (February 2021) - Shao, Ruiqi; Cheng, Longdi; Xue, Wenliang; Yu, Yanping; Pan, Ning
The spinning triangle is an important area in the spinning process, and the shape of the spinning triangle influences the yarn qualities. This paper aims to theoretically study the effects of the spinning parameters on the shape of the spinning triangle. In this paper, a model of the spinning triangle considering force equilibrium and torque equilibrium was built. The initial strain of fibers in the spinning triangle was determined by the profile of the spinning triangle. The initial height of the spinning triangle was obtained by the width of the spinning triangle and the twist angle. Based on the initial condition and boundary condition in the model, the displacements of the twisting point were obtained. With the displacements of the twisting point, the height of the spinning triangle and the deviation angle of the center fiber in the final spinning triangle, which represent the shape of the spinning triangle, were calculated. In the analysis, the spinning tension, yarn twist, and yarn radius were chosen as the independent parameters to analyze the geometric change of the spinning triangle.